A New Remotely Operated Sensor Platform for Interdisciplinary Observations under Sea Ice - Katlein, Christian; Schiller, Martin; Belter, Hans J.; Coppolaro, Veronica; Wenslandt, David; Nicolaus, Marcel (Frontiers in Marine Science, 2017)
Observation of the climate and ecosystem of ice covered polar seas is a timely task for the scientific community. The goal is to assess the drastic and imminent changes of the polar sea ice cover induced by climate change. Retreating and thinning sea ice affects the planets energy budget, atmospheric and oceanic circulation patterns as well as the ecosystem associated with this unique habitat. To increase the observational capabilities of sea ice scientists, we equipped a remotely operated vehicle (ROV) as sensor platform for interdisciplinary research at the ice water interface. Here we present the technical details and operation scheme of the new vehicle and provide data examples from a first campaign in the Arctic in autumn 2016 to demonstrate the vehicle’s capabilities. The vehicle is designed for efficient operations in the harsh polar conditions. Redundant modular design allows operation by three scientists simultaneously operating a wide variety of sensors. Sensors from physical, chemical and biological oceanography are combined with optical and acoustic sea ice sensors to provide a comprehensive picture of the underside of sea ice. The sensor suite provides comprehensive capabilities and can be further extended as additional ports for power and communication are available. The vehicle provides full six degrees of freedom in navigation, enabling intervention and manipulation skills despite its simple one function manipulator arm.